Comparison of CellSearch versus Parsortix circulating tumor cell enumeration and molecular characterization: A pilot study in metastatic prostate cancer patients - Jenna Kitz; Kelly Seto; Pinki Nandi; Paul Smith; David Englert; Ayten Hijazi; Michael Lock; Glenn S. Bauman; Scott Ernst; Ricardo Fernandes; Alison L. Allan (Next Research, 2025)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Tide–surge interaction observed at Singapore and the east coast of Peninsular Malaysia using a semi-empirical model - Zhi Yang Koh; Benjamin S. Grandey; Dhrubajyoti Samanta; Adam D. Switzer; Benjamin P. Horton; Justin Dauwels; Lock Yue Chew (Ocean Science, 2024)
Tide–surge interaction plays a substantial role in determining the characteristics of coastal water levels over shallow regions. We study the tide–surge interaction observed at seven tide gauges along Singapore and the east coast of Peninsular Malaysia, focusing on the timing of extreme non-tidal residuals relative to tidal high water. We propose a modified statistical framework using a no-tide–surge interaction (no-TSI) null distribution that accounts for asymmetry and variation in the duration of tidal cycles. We find that our modified framework can mitigate false-positive signals of tide–surge interaction in this region. We find evidence of tide–surge interaction at all seven locations, with characteristics varying smoothly along the coastline: the highest non-tidal residuals are found to occur most frequently before tidal high water in the south, both before and after tidal high water in the central region, and after tidal high water in the north. We also propose a semi-empirical model to investigate the effects of tidal-phase alteration, which is one mechanism of tide–surge interaction. Results of our semi-empirical model reveal that tidal-phase alteration caused by storm surges is substantial enough to generate significant change in the timing of extreme non-tidal residuals. To mitigate the effect of tidal-phase alteration on return level estimation, skew surge can be used. We conclude that (1) tide–surge interaction influences coastal water levels in this region, (2) our semi-empirical model provides insight into the mechanism of tidal-phase alteration, and (3) our no-TSI distribution should be used for similar studies globally.

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Optimization of operational parameters using RSM, ANN, and SVM in membrane integrated with rotating biological contactor - Sharjeel Waqas; Noorfidza Yub Harun; Ushtar Arshad; Afiq Mohd Laziz; Serene Lock Sow Mun; Muhammad Roil Bilad; Nik Abdul Hadi Nordin; Ahmad S. Alsaadi (Chemosphere, 2024)

Energy-efficient single-stage membrane rotating biological contactor for wastewater treatment - Sharjeel Waqas; Noorfidza Yub Harun; Serene Sow Mun Lock; Ahmad S. Alsaadi (Bioresource Technology Reports, 2024)

Lung-Brain Crosstalk in Sepsis: Protective Effect of Prophylactic Physical Exercise Against Inflammation and Oxidative Stress in Rats - Amanda Della Giustina; Judite Filgueiras Rodrigues; Erick Bagio; Sandra Bonfante; Larissa Joaquim; Graciela Zarbato; Solange Stork; Richard Simon Machado; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Khiany Mathias; Carlos Dacoregio; et al. (Molecular Neurobiology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

NESSCA Validation and Responsiveness of Several Rating Scales in Spinocerebellar Ataxia Type 2 - Thais L. Monte; Estela R. Reckziegel; Marina C. Augustin; Amanda S. P. Silva; Lucas D. Locks-Coelho; Orlando Barsottini; José L. Pedroso; Fernando R. Vargas; Maria-Luiza Saraiva-Pereira; Vanessa Bielefeldt Leotti; Laura Bannach Jardim (The Cerebellum, 2017)

Amino acid composition, protein content, and nitrogen-to-protein conversion factors of 21 seaweed species from Norwegian waters - I. Biancarosa; M. Espe; C. G. Bruckner; S. Heesch; N. Liland; R. Waagbø; B. Torstensen; E. J. Lock (Journal of Applied Phycology, 2017)

ATXN3, ATXN7, CACNA1A, and RAI1 Genes and Mitochondrial Polymorphism A10398G Did Not Modify Age at Onset in Spinocerebellar Ataxia Type 2 Patients from South America - Fernanda S. Pereira; Thais L. Monte; Lucas D. Locks-Coelho; Amanda S. P. Silva; Orlando Barsottini; José L. Pedroso; Mario Cornejo-Olivas; Pilar Mazzetti; Clecio Godeiro; Fernando R. Vargas; Maria-Angélica F. D. Lima; Hélio van der Linden; et al. (The Cerebellum, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Distribution of corticotectal cells in macaque - T. M. Lock; J. S. Baizer; D. B. Bender (Experimental Brain Research, 2003)

Water resources management in the Aral Basin: a river basin management model for the Syr Darya - S. Heaven; G. B. Koloskov; A. C. Lock; T. W. Tanton (Irrigation and Drainage, 2002)
The Aral Sea environmental crisis has been created by poor water management in the river basins of the Amu Darya and Syr Darya. Nearly all the flow is abstracted for ailing irrigation schemes in the upper and middle basins, for massive river basin transfer schemes, or is lost to evaporation and seepage from reservoirs and canals. The only solution to the crisis in the lower deltas is to allow more water to flow to them. The paper argues that the only practical approach for achieving this in the short to medium term is better water management in the upper and middle river basins, and that a more rational basis for allocating water to meet the needs of all users is urgently required. The paper describes a real‐time water resources management model for the Syr Darya river that has been designed for sustainable planning and management of the water resources to meet the needs of all riparian users. The power and limitations of such models in relation to effective management of the water resources of the Aral Basin are discussed. Copyright © 2002 John Wiley & Sons, Ltd.

A bymovirus PCR primer and partial nucleotide sequence provides further evidence for the recognition of rice necrosis mosaic virus as a bymovirus - J.L. Badge; S. Kashiwazaki; S. Lock; G.D. Foster (European Journal of Plant Pathology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

The role of glutathione in L -2-chloropropionic acid induced cerebellar granule cell necrosis in the rat - I. Wyatt; Andrew Gyte; Michael G. Simpson; Peter S. Widdowson; Edward A. Lock (Archives of Toxicology, 1996)

Glutathione depletion in the liver and brain produced by 2-chloropropionic acid: relevance to cerebellar granule cell necrosis - I. Wyatt; Andrew Gyte; G. Mainwaring; Peter S. Widdowson; E. A. Lock (Archives of Toxicology, 1996)

Effects of water-borne cadmium on the skin of the common carp (Cyprinus carpio) - Y. Iger; R. A. C. Lock; J. C. A. van der Meij; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1994)

Effect of waterborne and dietary cadmium on plasma ions of the teleostOreochromis mossambicus in relation to water calcium levels - H. B. Pratap; H. Fu; R. A. C. Lock; S. E. Wendelaar Bonga (Archives of Environmental Contamination and Toxicology, 1989)

Deacetylation and further metabolism of the mercapturic acid of hexachloro-1,3-butadiene by rat kidney cytosol in vitro - Iona S. Pratt; Edward A. Lock (Archives of Toxicology, 1988)

Sexuality in mucorales - J. D. Bu'Lock; B. E. Jones; S. A. Quarrie; D. J. Winstanley (Archives of Microbiology, 1974)